(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the effectiveness of modern pedagogical and methodological approaches used to develop the general physical preparedness of students majoring in Physical Education. The study examined the content of training sessions, load dynamics, individualized approaches, functional readiness indicators, and pedagogical monitoring tools. The findings indicate that methodologies developed on the basis of an integrated approach significantly improve students’ strength, endurance, agility, and speed. The article also provides practical methodological recommendations.